PENGARUH OPEN-ENDED LEARNING BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SD - Septi Nurul Hasanah; Siti Maryam Rohimah; Moh. Nurhadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low cognitive abilities and limited spatial visualization abilities of students in identifying and solving abstract non-routine word problems are the background of this research. These operational problems trigger the failure of elementary school children in designing systematic mathematical problem-solving strategies. The main focus of this scientific study is to detect the profound influence of the application of an open-ended learning pattern assisted by augmented reality technology in boosting the mathematical problem-solving abilities of elementary school students. This quantitative research path applies a quasi-experimental method with a nonequivalent control group design scheme. A total of 44 fifth-grade students in the elementary school environment were involved as observation subjects through a purposive sampling technique, then analyzed using the non-parametric Mann-Whitney U statistical test. Quantitative data from the final evaluation (posttest) empirically revealed a very clear disparity in performance, where the experimental group successfully achieved an average score of 73.33, while the control class only obtained a score of 61.30. The measurement of the effect size (effect size) of the correlation coefficient produced a score of 0.36, which indicates the strength of the effect is in the medium category (medium effect). The main conclusion confirms that the collaboration of an open learning approach with real-time virtual objects effectively stimulates independent critical thinking based on all Polya stage indicators. Education practitioners are recommended to utilize this interactive instrument as an alternative adaptive instructional strategy to ensure the comprehensive and sustainable success of the modern numeracy transformation agenda. ABSTRAK Rendahnya kecakapan kognitif serta keterbatasan kemampuan visualisasi spasial murid dalam mengidentifikasi dan memecahkan soal cerita non-rutin yang abstrak melatarbelakangi penelitian ini. Masalah operasional tersebut memicu adanya kegagalan anak usia dasar dalam merancang strategi penyelesaian matematika yang sistematis. Fokus utama kajian ilmiah ini adalah mendeteksi pengaruh mendalam dari penerapan pola open-ended learning berbantuan teknologi augmented reality dalam mendongkrak kemampuan pemecahan masalah matematik siswa sekolah dasar. Jalur riset kuantitatif ini menerapkan metode kuasi eksperimen berskema nonequivalent control group design. Sebanyak 44 murid kelas V di lingkungan sekolah dasar tersebut dilibatkan sebagai subjek amatan melalui teknik sampling purposive, lalu dianalisis menggunakan uji statistik non-parametrik Mann-Whitney U. Data kuantitatif hasil evaluasi akhir (posttest) secara empiris menyingkap disparitas performa yang sangat nyata, di mana kelompok eksperimen sukses meraih rerata nilai sebesar 73,33, sedangkan kelas kontrol hanya memperoleh angka 61,30. Pengukuran ukuran efek (effect size) koefisien korelasi menghasilkan skor sebesar 0,36, yang mengindikasikan kekuatan pengaruh berada pada kategori sedang (medium effect). Simpulan utama menegaskan bahwa kolaborasi pendekatan pembelajaran terbuka dengan objek virtual secara real-time efektif menstimulasi kemandirian berpikir kritis berdasarkan seluruh indikator tahapan Polya. Praktisi pendidikan direkomendasikan memanfaatkan instrumen interaktif ini sebagai alternatif strategi instruksional adaptif untuk menyukseskan agenda transformasi numerasi modern secara menyeluruh dan berkelanjutan.